SINAS: Effective Impact in the Quality Improvement of Ambulatory Surgery at an Ambulatory Centre - Eurico Castro Alves; Teresa Correia; Pedro Brandão; Laetitia Teixeira; Ana Povo (Acta Médica Portuguesa, 2020)
Introduction: The National Health Assessment System is a system designed by the Portuguese Health Regulatory Entity in order to evaluate the overall quality of the health care institutions. One of the key areas evaluated by the National Health Assessment System is ambulatory surgery. The aim of this study is to demonstrate that the introduction of the National Health Assessment System evaluation at our ambulatory centre not only improved the overall quality of ambulatory surgery but also the quality of the clinical record entries. Material and Methods: A retrospective analysis was performed from the hospital’s clinical database. The study was carried out at the ambulatory centre of the Hospital and University Centre of Porto, and included 100 consecutive surgical procedures, across all surgical specialties, previously selected by the National Health Assessment System audit performed in 2015 in our ambulatory surgery centre and other 46 surgical procedures performed in 2008 at our hospital, before the National Health Assessment System was implemented. The main outcome measure was the validation and record of the seven indicators of National Health Assessment System for ambulatory surgery. Results: We have seen an improvement in all indicators after the National Health Assessment System implementation, except for criterion 4. Discussion: Our study demonstrates that the introduction of the National Health Assessment System in our ambulatory centre resulted in the improvement in the quality of both of clinical practice, and clinical record keeping Conclusion: We can conclude that the application of evaluation of quality indicators and benchmarking practices can be used to enhance healthcare outcomes.